Parametric Modeling and Stability Analysis of Temporary Grandstand - He, Lin; Wu, Zhen Yu; Liu, Cong (Applied Mechanics and Materials, 2014)
Temporary grandstands bear crowd load, which is created when spectators jumping on the structure. The simplified loads applied to temporary grandstand have been obtained based on experiment data of human body jumping forces. By the ABAQUS software, the parametric and automatic modeling of three-dimensional (3D) temporary grandstand structures has been realized with Python scripting. The linear buckling analysis and nonlinear buckling analysis of the structure have been carried out. The ultimate bearing capacity and the structural deformation under crowd load have been acquired. Results show that the nonlinear effect of the structure under crowd load is very obvious; the linear buckling analysis cannot get the ultimate bearing capacity of the structure and the first order buckling mode cannot simulate the final deformation of the structure either. The research of this paper greatly improve the efficiency of the construction and automation design of temporary structures and reveal the mechanical behavior of such structure to a certain degree.